HISTOPATHOLOGICAL AND MICROBIAL STUDY OF APPENDIX IN EMERGENCY APPENDICECTOMY PATIENTS (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Acute appendicitis is one of the most common surgical emergencies worldwide. Despite advances in imaging and clinical diagnosis, histopathological examination (HPE) remains the gold standard for confirmation, while microbiological profiling helps in understanding the infectious etiology and guiding antibiotic therapy. Aims and Objectives: The aim of this study was to evaluate the histopathological and microbiological findings of appendix specimens in emergency appendicectomy patients and to correlate them with clinical and radiological features for better diagnostic understanding and management of acute appendicitis. Materials and Methods: The present study was a hospital-based longitudinal follow-up study conducted in the emergency setting of the Department of General Surgery, Calcutta National Medical College and Hospital. The study was carried out over a period of one year and included patients operated for acute appendicitis admitted to the department. The estimated sample size was approximately 100 patients. Results: The study (N=100) showed equal gender distribution (female 51%, male 49%) with most patients aged 21–30 years (38%) and mean age 30.39 ± 9.48 years. RIF pain with vomiting was the main symptom (46%). USG showed elongated tubular structure (38%), microbiology mainly E. coli and Pseudomonas (26% each), and HPE most commonly lymphocytic infiltration (52%) and faecolith (36%), confirming inflammatory appendicular disease in young adults. Conclusion: Appendicular disease mainly affects young adults with equal gender distribution and commonly presents with RIF pain and vomiting. Findings support an inflammatory etiology confirmed by imaging, microbiology, and histopathology, highlighting the need for early diagnosis and management.